Durable and regenerable superhydrophobic coatings for brass surfaces with excellent self-cleaning and anti-fogging properties prepared by immersion technique. (July 2018) - Varshney, Priya; Mohapatra, Soumya S.
Abstract: In this work, superhydrophobic coatings on brass surfaces were prepared by two-step (chemical etching with a mixture of hydrochloric and nitric acids, followed by treatment with lauric acid) and one-step (treatment with lauric acid). The surface morphology shows the presence of rough microstructures on treated brass surfaces. Superhydrophobicity with high water static contact (>173°)and low sliding angles (<4°) is achieved by both processes. Besides, the dynamics of water droplets on the coated samples also were studied. Additionally, the durability of the coatings also was examined by performing thermal, chemical, and mechanical stability tests. Along with, these coatings are also found to be excellent regeneration ability as verified experimentally. Further, coatings exhibit self-cleaning and anti-fogging properties. Highlights: Fabrication of superhydrophobic coatings on brass substrates using immersion technique. Study the water droplets dynamics on the coated samples. Coatings are found thermal, chemical, and mechanical stable. Coatings exhibit self-cleaning and anti-fogging properties.